Simultaneous Estimation of Ibuprofen and Famotidine in Pure and Combination Dosage Form by RP-HPLC - Narendra Nyola, Govinda Samy Jeyabalan (Journal of Applied Pharmaceutical Science)
A new simple, accurate, precise and reproducible RP-HPLC method has been developed for the simultaneous estimation of ibuprofen and famotidine in tablet dosage forms using C18 column (Phenomenex, 250 x 4.6 mm, 5 µm) in isocratic mode. The mobile phase consisted of Methanol: Water: Phosphate buffer in the ratio of 70:20:10 (v/v/v). The flow rate was 1.0 ml/min and detection wavelength was carried out at 284 nm. The retention times of ibuprofen and famotidine were 3.6 min and 7.8 min, respectively. The method was linear over the concentration range for ibuprofen 2-10 µg/ml and for and famotidine 2-10 µg/ml. The recoveries of ibuprofen and famotidine were found to be in the range of 99.037-100.766% and 99.703-100.433% respectively. The validation of method was carried out utilizing ICHguidelines. The described HPLC method was successfully employed for the analysis of pharmaceutical formulations containing combined dosage form.
Keywords: Simultaneous estimation,RP-HPLC,ibuprofen,famotidine.